Fully automated imaging protocol independent system for pituitary adenoma segmentation: a convolutional neural network-based model on sparsely annotated MRI - Černý, Martin; Kybic, Jan; Májovský, Martin; Sedlák, Vojtěch; Pirgl, Karin; Misiorzová, Eva; Lipina, Radim; Netuka, David (Neurosurgical review, 2023)
This study aims to develop a fully automated imaging protocol independent system for pituitary adenoma segmentation from magnetic resonance imaging (MRI) scans that can work without user interaction and evaluate its accuracy and utility for clinical applications. We trained two independent artificial neural networks on MRI scans of 394 patients. The scans were acquired according to various imaging protocols over the course of 11 years on 1.5T and 3T MRI systems. The segmentation model assigned a class label to each input pixel (pituitary adenoma, internal carotid artery, normal pituitary gland, background). The slice segmentation model classified slices as clinically relevant (structures of interest in slice) or irrelevant (anterior or posterior to sella turcica). We used MRI data of another 99 patients to evaluate the performance of the model during training. We validated the model on a prospective cohort of 28 patients, Dice coefficients of 0.910, 0.719, and 0.240 for tumour, internal carotid artery, and normal gland labels, respectively, were achieved. The slice selection model achieved 82.5% accuracy, 88.7% sensitivity, 76.7% specificity, and an AUC of 0.904. A human expert rated 71.4% of the segmentation results as accurate, 21.4% as slightly inaccurate, and 7.1% as coarsely inaccurate. Our model achieved good results comparable with recent works of other authors on the largest dataset to date and generalized well for various imaging protocols. We discussed future clinical applications, and their considerations. Models and frameworks for clinical use have yet to be developed and evaluated.
Keywords: Pituitary Neoplasms; adenom; Magnetic Resonance Imaging; Adenoma; Image segmentation; lidé; Neural Networks, Computer; Machine learning; Magnetic resonance imaging; prospektivní studie; počítačové zpracování obrazu; magnetická rezonanční tomografie; Prospective Studies; Pituitary adenoma; nádory hypofýzy; neuronové sítě; Image Processing, Computer-Assisted; Humans